"God Hates Your Feelings": Neutralizing Emotional Deviance within the Westboro Baptist Church. Issue 12 (2nd December 2017) - Powell-Williams, Todd; Powell-Williams, Melissa
Abstract: Drawing on individual and peer-group interviews, participant observations, and analysis of media content, we examine the habitual emotional deviance and neutralization techniques employed by the Westboro Baptist Church. We argue that their notoriety is attributed to their persistent, intentional, and unapologetic disregard for cultural feeling rules including incongruous emotional responses to events, fusion of culturally oppositional sentiments, and denigration of "sacred" groups and symbols. Interviews reveal that while claiming to embrace their deviant status, members engage in common neutralization techniques including denial of responsibility for the pain and discomfort they cause, appealing to higher loyalties, and denial of victimization.